2016
DOI: 10.1111/aos.13254
|View full text |Cite
|
Sign up to set email alerts
|

Validity of aqueous flare measurement in predicting proliferative vitreoretinopathy in patients with rhegmatogenous retinal detachment

Abstract: Preoperative aqueous flare is a strong predictive factor for PVR redetachment. The laser flare-cell meter provides a fast and safe tool to accurately identify patients at risk for postoperative PVR, especially when clinical examination did not predict this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…Anterior chamber aqueous flarea surrogate marker for inflammation -has been proposed as a predictor for PVR in patients with a RRD (Schroder et al 2012;Hoerster et al 2013;Conart et al 2017). In contrast to previous reports, we recently reported that the preoperative aqueous flare value is not a strong predictor for the development of PVR postoperatively (Mulder et al 2017).…”
Section: Introductioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Anterior chamber aqueous flarea surrogate marker for inflammation -has been proposed as a predictor for PVR in patients with a RRD (Schroder et al 2012;Hoerster et al 2013;Conart et al 2017). In contrast to previous reports, we recently reported that the preoperative aqueous flare value is not a strong predictor for the development of PVR postoperatively (Mulder et al 2017).…”
Section: Introductioncontrasting
confidence: 73%
“…Adding the outcome of postoperative aqueous flare measurements to existing risk prediction models could possibly increase its value. The size of a detachment is a well-known risk factor for the development of PVR, but the size of the detachment is also correlated with flare (Schroder et al 2012;Conart et al 2017). In our study, this association was the strongest for preoperative flare and higher number of quadrants detachment (r s = 0.42, p < 0.001), and for postoperative flare, this association was weak (r s = 0.20, p = 0.005).…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Therefore, non-invasive laser flare photometry has been established as a possible tool for fast and precise estimation of high-risk patients for PVR re-detachments [ 15 ]. Conart et al recently confirmed that preoperative aqueous flare seems to be a major predictive factor for PVR re-detachment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%